Protocol: a realist review of user fee exemption policies for health services in Africa. Issue 1 (24th January 2012) - Robert, Emilie; Ridde, Valéry; Marchal, Bruno; Fournier, Pierre
Abstract : Background: Four years prior to the Millenium Development Goals (MDGs) deadline, low- and middle-income countries and international stakeholders are looking for evidence-based policies to improve access to healthcare for the most vulnerable populations. User fee exemption policies are one of the potential solutions. However, the evidence is disparate, and systematic reviews have failed to provide valuable lessons. The authors propose to produce an innovative synthesis of the available evidence on user fee exemption policies in Africa to feed the policy-making process. Methods: The authors will carry out a realist review to answer the following research question: what are the outcomes of user fee exemption policies implemented in Africa? why do they produce such outcomes? and what contextual elements come into play? This type of review aims to understand how contextual elements influence the production of outcomes through the activation of specific mechanisms, in the form of context–mechanism–outcome configurations. The review will be conducted in five steps: (1) identifying with key stakeholders the mechanisms underlying user fee exemption policies to develop the analytical framework, (2) searching for and selecting primary data, (3) assessing the quality of evidence using the Mixed-Method Appraisal Tool, (4) extracting the data using the analytical framework and (5) synthesising the data in the form of context–mechanism–outcomes configurations. The output will be a middle-range theory specifying how user fee exemption policies work, for what populations and under what circumstances. Ethics and dissemination: The two main target audiences are researchers who are looking for examples to implement a realist review, and policy-makers and international stakeholders looking for lessons learnt on user fee exemption. For the latter, a knowledge-sharing strategy involving local scientific and policy networks will be implemented. The study has been approved by the ethics committee of the CHUM Research Centre (CR-CHUM). It received funding from the Canadian Institutes of Health Research. The funders will not have any role in study design; collection, management, analysis, and interpretation of data; writing of the report and the decision to submit the report for publication, including who will have ultimate authority over each of these activities.